LATAR BELAKANG MENINGKATNYA SIKAP ANTI YAHUDI DI RUSIA (PERIODE 2000 - 2004 ) - Rika Ikawati (Universitas Muhammadiyah Yogyakarta, 2005)
LATAR BELAKANG MENINGKATNYA SIKAP ANTI YAHUDI DI RUSIA (PERIODE 2000 - 2004 )